Pengaruh Sistem Informasi Manajemen dan Lingkungan Kerja Terhadap Kinerja Pegawai di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Medan - Maria Magdalena Rouli Boru Harianja; Simson Ginting (Department of Public Administration, Muhammadiyah University of Makassar, 2023)
Achieving the goals of an organization is often associated with human resources who have good performance. Producing good performance is of course driven by various factors, so this study aims to examine the effect of management information system and the work environment on employee performance at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Medan. This research method is associative research with a quantitative approach. As for the sampling using the purposive sampling technique that has been obtained as many as 37 employees as respondents who use the SIPANDU MEDAN application. From the results of the research calculations, it can be seen that management information system variables (X1) and work environment (X2) partially and simultaneously have a positive and significant effect on employee performance (Y). Evidenced by the value of tcount ˃ ttable (2,032), Fcount ˃ Ftable (3,27) and α of 0,00 ˂ 0,05. In addition, the results of the test for the coefficient of determination (R2) also show that the value of the influence of management information system and the work environment on employee performance is 66,3% (0,663) and the remaining 33,7% is influenced by other variables not discussed in this research.